2003
DOI: 10.1271/bbb.67.170
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation by Caffeic Acid, Coumalic Acid, and Corilagin of the Germination of Resting Spores of the Clubroot PathogenPlasmodiophora brassicae

Abstract: Some chemicals were examined for their eŠects on the germination of resting spores of the clubroot pathogen Plasmodiophora brassicae, and on the control of clubroots in Chinese cabbage. CaŠeic acid, coumalic acid, and corilagin stimulated the germination of Plasmodiophora spores and prevented the formation of clubroots in Chinese cabbage. Clubroot might be controlled by agents with germination-stimulating eŠects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 8 publications
1
8
0
Order By: Relevance
“…Features of S. subterranea resting spore dormancy observed in this study were similar to those reported for P. brassicae (Ohi et al. ; Friberg et al. ) .…”
Section: Discussionsupporting
confidence: 90%
“…Features of S. subterranea resting spore dormancy observed in this study were similar to those reported for P. brassicae (Ohi et al. ; Friberg et al. ) .…”
Section: Discussionsupporting
confidence: 90%
“…This finding was supported by the evidence of root exudates from Brassica host (broccoli) and non-Brassica host (ryegrass), both stimulated spore germination [46]. Studies also reported that some specific stimulants such as caffeic acid, coumalic acid, corilagin, and others could stimulate resting spore germination in Chinese cabbage [47,48]. All these studies suggest that the Brassica species have unique root characteristics which permit pathogen invasion and subsequent infection for the disease development.…”
Section: Host-pathogen Interactions a During Resting Spore Germinationmentioning
confidence: 71%
“…Compounds in the first component may occur universally in the root exudates of hosts and nonhosts. It is probable that caffeic acid, coumalic acid and corilagin, identified by Ohi et al . (2003), are among these compounds.…”
Section: Discussionmentioning
confidence: 95%
“…Compounds in the first component may occur universally in the root exudates of hosts and nonhosts. It is probable that caffeic acid, coumalic acid and corilagin, identified by Ohi et al (2003), are among these compounds. For the second GSF component, the involvement of enzymatic activity not only generates stimulatory chemicals, but also provides a potential avenue for the pathogen to recognize its host.…”
Section: Molecular Mechanism Of Resting Spore Germination Stimulationmentioning
confidence: 99%